6
$\begingroup$

How do you calculate the following limits?

$$\lim_{n \to \infty} \left(1 + \frac{1}{n!}\right)^n$$ $$\lim_{n \to \infty} \left(1 + \frac{1}{n!}\right)^{n^n}.$$

I really don't have any clue about how to proceed: I know the famous limit that defines $e$ ($\lim_{n \to \infty} \left(1 + \frac{1}{n}\right)^n=e$), but the factorials (and the exponent of the second one) here throw me off. Any ideas?

$\endgroup$
3
$\begingroup$

HINT: $$ \lim_{n \to \infty} \left(1 + \frac{1}{n!}\right)^n=\lim_{n \to \infty} \left(\left(1 + \frac{1}{n!}\right)^{n!}\right)^{n/n!} $$ and the inner limit is $e$, hence the final one is 1. The second case is similar.

$\endgroup$
  • $\begingroup$ Oh, ok. I see it now. Thank you very much! :) $\endgroup$ – user62029 May 23 '15 at 22:25
  • 3
    $\begingroup$ I don't think you can do this $\endgroup$ – Alex May 23 '15 at 22:25
  • $\begingroup$ @Alex Why not ? $\endgroup$ – user62029 May 23 '15 at 22:26
  • $\begingroup$ @Kola B. you are taking a limit inside $()^{\frac{n}{n!}}$, you can't do this like this $\endgroup$ – Alex May 23 '15 at 22:36
  • $\begingroup$ @Alex It looks suspicious, but $f(x,y)=x^y$ is continuous at $(x,y)=(e,1)$ which justifies separating the limit into the inner and outer components as is done here. (It's also continuous, in the extended reals, at $(e,\infty)$). We only get trouble by $(1,\infty)$ and $(0,0)$, at least when $x\geq 0$. $\endgroup$ – Milo Brandt May 23 '15 at 22:36
4
$\begingroup$

First limit is easy. Let $$f(n) = \left(1 + \frac{1}{n!}\right)^{n}$$ We will use the fact that the sequence $a_{n} = (1 + (1/n))^{n}$ is strictly increasing for $n \geq 3$ and tends to a positive limit (when $n \to \infty$) denoted by $e$. Also $2 < e < 3$. These facts can be proven (and given in many textbooks) without any standard theory of logarithms and exponentials. Another fact which we need to know is that if $A > 0$ then $A^{1/n}$ tends to $1$ as $n \to \infty$.

We thus have $a_{n} = (1 + (1/n))^{n} < e$ for all $n$. Replacing $n$ by $n!$ we get that $(1 + (1/n!))^{n!} < e$. Hence we can see that $$1 < f(n) = \left(1 + \frac{1}{n!}\right)^{n} = \left(\left(1 + \frac{1}{n!}\right)^{n!}\right)^{1/(n - 1)!} < e^{1/(n - 1)!}$$ Again it is easy to prove that $1/(n - 1)! < 1/n$ for all $n > 3$ and hence we have $$1 < f(n) < e^{1/n}$$ for $n > 3$. Letting $n \to \infty$ and using Squeeze theorem we get $f(n) \to 1$ as $n \to \infty$.


For the function $$g(n) = \left(1 + \frac{1}{n!}\right)^{n^{n}}$$ we need to use the fact that $$a_{n} = \left(1 + \frac{1}{n}\right)^{n} \geq 2$$ for $n$. Replacing $n$ by $n!$ we get $$\left(1 + \frac{1}{n!}\right)^{n!} \geq 2$$ for all $n$. And then we can see that $$g(n) = \left(1 + \frac{1}{n!}\right)^{n^{n}} = \left(\left(1 + \frac{1}{n!}\right)^{n!}\right)^{n^{n}/n!}\geq 2^{n^{n}/n!}\tag{1}$$ We next need to analyze the sequence $n^{n} / n!$. It turns out it is simpler to handle its reciprocal $b_{n} = n!/n^{n}$. Clearly $$\frac{b_{n + 1}}{b_{n}} = \frac{(n + 1)!}{(n + 1)^{n + 1}}\cdot\frac{n^{n}}{n!} = \dfrac{1}{\left(1 + \dfrac{1}{n}\right)^{n}} \to \frac{1}{e} < 1$$ and hence the series $\sum b_{n}$ is convergent (Ratio test) and hence $b_{n} \to 0$.

It follows that $1/b_{n} \to \infty$ as $n \to \infty$. It also follows that $2^{1/b_{n}} \to \infty$ as $n \to \infty$. From $(1)$ we see that $g(n) \geq 2^{1/b_{n}}$ and hence $g(n) \to \infty$ as $n \to \infty$.


Note: From the above it is seen that in most cases basic limit theorems and certain standard limits are sufficient to solve a problem without invoking advanced results. In this case for example we dealt with limits involving variable exponents like $n!$ and $n^{n}$ and yet their solution was possible without any theory of exponentials and logarithms. Unless we have to deal with irrational exponents (or say complex/imaginary) it does not make sense to invoke the general theory of logarithm and exponential.

$\endgroup$
0
$\begingroup$

Consider the first expression $$A=\left(1 + \frac{1}{n!}\right)^n$$ So $$\log(A)=n\log\left(1 + \frac{1}{n!}\right)\approx \frac n{n!}=\frac 1{(n-1)!}$$ So, $\log(A)$ goes to $0$ and then $A$ to $1$.

Consider the second expression $$B_n=\left(1 + \frac{1}{n!}\right)^{n^n}$$ So $$\log(B)={n^n}\log\left(1 + \frac{1}{n!}\right)\approx \frac {n^n}{n!}$$ Now, use Stirling approximation $$n!\approx {n^n}\sqrt{2\pi n}e^{-n}$$ So, $$\log(B)\approx \frac {n^n}{{n^n}\sqrt{2\pi n}e^{-n}}=\frac {e^n}{\sqrt{2\pi n}}$$ So, $\log(B)$ goes to $\infty$ and then $B$ to $\infty$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.